1999
DOI: 10.1246/cl.1999.821
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) Iodide-Promoted Allylation of Allyl- and Vinyl-silanes Assisted by Intramolecular-Coordination

Abstract: The allylation products, 1-(2-pyridylthio)alk-1,5-dienes, were produced regioselectively when 1-(2-pyridylthio)-1-(trimethylsilyl)alk-2-enes were treated with allylic chlorides in the presence of CuI and KF. The similar reaction of 1-(2-pyridylthio)-1-(trimethylsilyl)alk-1-enes with allylic chlorides produced the 1,4-dienes with complete retention of configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Although Z -isomers of 3 are prepared via 1,4 O-to-C sp 2 silyl migration,7a the method requires multistep transformation. Therefore, we first established the stereoselective preparation of Z -3 by the reaction sequence similar to that employed for the synthesis of ( Z )-β-(tributylstannyl)-α,β-unsaturated ketones 10a…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Z -isomers of 3 are prepared via 1,4 O-to-C sp 2 silyl migration,7a the method requires multistep transformation. Therefore, we first established the stereoselective preparation of Z -3 by the reaction sequence similar to that employed for the synthesis of ( Z )-β-(tributylstannyl)-α,β-unsaturated ketones 10a…”
Section: Resultsmentioning
confidence: 99%
“…In the course of study on the preparation and synthetic application of group 14 vinylmetal species, we found that vinylsilanes possessing a 2-pyridylthio group at the carbon α to the trimethylsilyl group reacted with allylic halides in the presence of CuI−KF to produce the cross-coupling products 10e. We tentatively assume that the reaction proceeds through transmetalation of silicon to copper assisted by the intramolecular coordination of nitrogen to silicon.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, we found that the vinylsilanes bearing a 2-pyridylthio group at the carbon α to the trimethylsilyl group reacted with allylic halides in the presence of CuI−KF to produce the cross-coupling products 5e. We tentatively assume that the reaction proceeds via transmetalation of silicon to copper assisted by the intramolecular coordination of nitrogen to silicon.…”
mentioning
confidence: 95%
“…In connection with our continuous study on the preparation and reaction of group 14 vinylmetals, we were intrigued with the 1,4 C sp 2 -to-O silyl migration of conformationally rigid γ-trimethylsilyl allylic alcohols 1a and 1b . Unlike the reaction of cinnamyl alcohol derivative 1d described above, the treatment of 1a and 1b with a stoichiometric or catalytic amount of lithium tert -butoxide at room temperature for 24 h gave the cyclic silyl ethers 1-oxa-2-silacyclopent-3-enes 2a and 2b as sole products (Scheme ).…”
mentioning
confidence: 99%
“…The allylation did not take place without CsF. Thus, we are currently assuming that the beneficial role of the pyridyl group is to help the reacting CC bond to coordinate to copper through precoordination (complex-induced proximity effect), thereby facilitating the subsequent Si-to-Cu transmetalation to generate allylcopper species by the action of CsF 1 Synthesis, crystal structure, and reaction of Cu complex 4 . …”
mentioning
confidence: 99%